(untitled) (Revista Nacional de Odontología, 2016)
The frequency of incisor molar hypomineralization is variable, which may be present in up to 25% of the population. Objective. To establish frequency and severity of MIH in a group of Mexican children. Material and Methods. A cross-sectional study was carried out in a convenience sample composed by 433 children between 8 and 12 years old, of both sexes. The survey looked at the clinical examination of the permanent first molars and incisors considering the criteria set by the European Academy of Paediatric Dentistry (EAPD), and severity criteria Mathu-Muju & Wright. For the epidemiological survey previously it was standardized to an examiner (kappa=0.93). Results: 13.9% of schoolchildren presented HIM, being more frequent in boys (8.1%) compared to girls (5.8%), associated with this variable (p=0.049). Categories of 8 and 10 years old had a higher number of cases of MIH, showing no statistical significance with the event of study. The first molars were found to be more involved in MIH patterns, also in terms of the severity of mild HIM was the most common condition. Conclusions. The frequency and severity observed shows a scenario in which need to be carried out monitoring of children with HIM by the risk posed to the establishment of dental caries.